Influência do modelo de fissuração na modelagem em elementos finitos de vigas de concreto armado - Pacheco, Thiago Mendonça (2014)
Concrete is a very versatile material widely used by the construction industry. However, the adequate application of your nonlinear behavior, by numerical methods is still a major challenge in structural engineering. In this workwas evaluated three methods of distributed crackingbased Fracture Mechanics: fixed rotational and multidirectional. , To this the flexural behavior of beam was simulated numerically by the commercial software DIANA ®, and compared with experimental results reported in the literature. For the beams that failed by bending, the numerical simulation for all three models shown agreement with experimental results with ability to predict the equilibrium path, the maximum load and deformation failure. However, to analysis of beams that failed by shear, the fixed crack model did not capture properly the rupture load and the rotational model presented numerical instability after the start of diagonal cracking. Moreover, the multidirectional model describes the complete load-displacement behavior and adequately predicts the appearance of diagonal cracks as well as the latest load and deformation.